The Impact of Virtual Reality on Cognitive Load Among Senior Students at Middle Technical University: An Empirical Study - Saif M Duhaim (Journal of Technology and System Information, 2026)
The adoption of Virtual Reality (VR) in higher education has gained increasing worldwide interest, however, its evaluation as an effect on workload and cognitive-load related learning outcomes for senior technical university students in Iraq is still an unaddressed issue. This study sought to fill the gap in the literature by investigating the effect of a VR-based instruction on the Nasa TlX workload indicators concerning the cognitive load, the effect of the presence and the intrinsic motivation on the learning performance of senior engineering students in a technical university in Baghdad. Employing a quasi-experimental pre-post control group design, 80 learners participated and were randomly assigned to either a VR group (n = 40) who experienced the interactive content through Meta Quest 2 HMDs or a control group (n = 40) who were taught in a traditional lecture style. The cognitive workload was assessed by NASA-TLX, and the analyses were performed with the use of independent-samples t-tests, MANOVA and exploratory Structural Equation modeling (SEM). Results showed that the VR group had significantly lower mental demand (M = 52.4vs. 61.7, p = .001) and frustration (M = 30.4vs. 44.8, p < .001), but the overall NASA-TLX workload index was not significantly different between the two groups (M = 49.65vs. 52.17, p = .184). The VR group outperformed in learning (MCQ: M = 23.4/30 vs. 19.7/30, d = 1.00), knowledge retention at one-week post-test (78.6% vs. 62.4%, d = 1.53), and intrinsic motivation scores. . Exploratory SEM analysis showed that the immersion in VR could promote learning indirectly by decreasing the extraneous-load-related workload (β = −.54) and enhancing presence (β = . 71). These results suggest that the VR-based intervention has the potential to improve certain aspects of the workload and learning outcomes in higher education in developing countries, although statements regarding an overall reduction in cognitive load should be considered with caution.